Reversible Respiratory Arrest without Anesthesiology Assistance after Retrobulbar Injection-A Case Report - Brown, Gary C; Brown, Melissa M; Milder, Eugene (Journal of Ophthalmology and Research, 2019)
Abstract not available in the source database.